Transport and Energy Deposition of hot Electrons through the Shock Ignition pre Compressed Target. Issue 10 (24th June 2016) - Rezaei, S.; Farahbod, A. H.; Jafari, M. J.
Abstract: Shock ignition as an alternative scheme of the laser fusion has the potential of achieving efficient implosion. However, hot electrons produced in result of ignitor‐corona interaction may penetrate deep into the fuel making the compression less effective. Transport and energy deposition of hot electron beam into the dense pre compressed of HiPER target by means of Monte Carlo approach are discussed considering the influence of real density and electron beam characteristics. The target parameters before igniting the hot spot have been extracted from a fluid code and used as the initial profile for Monte Carlo simulations. In comparison with simplified step like density profile, electrons penetrate slightly deeper in the case of real shaped density profile. In addition, deposition zone of a broad spectrum electron beam is wider while, monoenergetic electrons depose their energy locally resulting more maximum energy deposition value. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)